Model Manajemen Rehabilitasi Infrastruktur Gedung Madrasah Tsanawiyah untuk Peningkatan Mutu Layanan Pendidikan di Kabupaten Konawe Kepulauan - Eliyanti Agus Mokodompit; La Ode Muhammad Ichwan Sjcahrawy; Rosmiati Rosmiati (Lembaga Yasin AlSys, 2025)
The infrastructure conditions of Madrasah Tsanawiyah (MTs) buildings in Konawe Kepulauan Regency are still marked by various problems, including damaged structures, limited classroom space, substandard sanitation facilities, and inadequate learning support amenities, all of which negatively impact the quality of educational services and constrain comfortable and effective learning activities. This study aimed to formulate a management model for MTs building rehabilitation that is effective, efficient, and oriented toward improving the quality of educational services. Adopting a qualitative approach with a case study design in several MTs in Konawe Kepulauan Regency, data were collected through in-depth interviews, field observations, and document analysis. The findings show that an ideal rehabilitation management system is supported by three main components: (1) planning based on the actual needs of the madrasah; (2) transparent and accountable rehabilitation governance; and (3) sustainable post-rehabilitation utilization and maintenance of buildings. The implementation of this model has been shown to improve the condition of facilities, create a safer and more conducive learning environment, and enhance the quality of educational services at the madrasah level. These findings provide practical contributions for local policymakers and administrators of Islamic educational institutions in designing more targeted and sustainable infrastructure rehabilitation programs.